Human Treponema pallidum 11q/j isolate belongs to subsp. endemicum but contains two loci with a sequence in TP0548 and TP0488 similar to subsp. pertenue and subsp. pallidum, respectively. - Lenka Mikalová; Michal Strouhal; Jan Oppelt; Philippe Alain Grange; Michel Janier; Nadjet Benhaddou; Nicolas Dupin; David Šmajs (Public Library of Science (PLoS), 2017)
BACKGROUND:Treponema pallidum subsp. endemicum (TEN) is the causative agent of endemic syphilis (bejel). An unusual human TEN 11q/j isolate was obtained from a syphilis-like primary genital lesion from a patient that returned to France from Pakistan. METHODOLOGY/PRINCIPAL FINDINGS:The TEN 11q/j isolate was characterized using nested PCR followed by Sanger sequencing and/or direct Illumina sequencing. Altogether, 44 chromosomal regions were analyzed. Overall, the 11q/j isolate clustered with TEN strains Bosnia A and Iraq B as expected from previous TEN classification of the 11q/j isolate. However, the 11q/j sequence in a 505 bp-long region at the TP0488 locus was similar to Treponema pallidum subsp. pallidum (TPA) strains, but not to TEN Bosnia A and Iraq B sequences, suggesting a recombination event at this locus. Similarly, the 11q/j sequence in a 613 bp-long region at the TP0548 locus was similar to Treponema pallidum subsp. pertenue (TPE) strains, but not to TEN sequences. CONCLUSIONS/SIGNIFICANCE:A detailed analysis of two recombinant loci found in the 11q/j clinical isolate revealed that the recombination event occurred just once, in the TP0488, with the donor sequence originating from a TPA strain. Since TEN Bosnia A and Iraq B were found to contain TPA-like sequences at the TP0548 locus, the recombination at TP0548 took place in a treponeme that was an ancestor to both TEN Bosnia A and Iraq B. The sequence of 11q/j isolate in TP0548 represents an ancestral TEN sequence that is similar to yaws-causing treponemes. In addition to the importance of the 11q/j isolate for reconstruction of the TEN phylogeny, this case emphasizes the possible role of TEN strains in development of syphilis-like lesions.